A wheel with reduced hardness of tread near surface layer and production method thereof

By adopting the 'weak-stop-strength' intermittent heat treatment cooling technology in the railway wheels, the problem of large surface hardness gradient is solved, the design of a narrow hardness range is realized, and the smooth operation of the vehicle is improved. and safety, and extend service life.

CN115558765BActive Publication Date: 2025-01-10МААНЬШАНЬ АЙРОН ЭНД СТИЛ КО ЛТД
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211184793.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-27
Publication Date
2025-01-10
Estimated Expiration
2042-09-27

AI Technical Summary

Technical Problem

Existing railway wheels are prone to surface damage under the influence of wheel-rail contact stress and vibration impact, resulting in a large hardness gradient and cannot meet the special supply requirements of the narrow hardness range, affecting the smoothness and safety of the vehicle.

Method used

The tread intermittent spray quenching is used, specifically the 'weak-stop-strong' intermittent heat treatment cooling. After the initial spray quenching is carried out by a small flow rate, the natural environment will be left to a large flow spray quenching to control the cooling speed to avoid non- The formation of harmful tissue of pearlite reduces the hardness of the near-surface layer of the tread.

Benefits of technology

It has achieved a reduction in the hardness of the near-surface layer of the wheel tread, narrowed the cross-sectional hardness range, meeting the requirements of the narrow hardness range, improving the early service performance of the wheel and the wear stability of the entire life cycle, extending the service life and reducing operation and maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115558765B_ABST
    Figure CN115558765B_ABST
Patent Text Reader

Abstract

The present invention provides a wheel and a production method thereof for reducing the hardness of the near-surface layer of the tread, which adopts an intermittent quenching method for the tread; that is, a "weak-stop-strong" intermittent heat treatment cooling is adopted, and the wheel tread is first sprayed with a flow rate L1. After the spraying of the flow rate L1 is completed, the wheel is left to stand at a natural ambient temperature for 5 to 15 seconds, and then the flow rate L2 is switched to spray the wheel tread; the flow rate L1 is 1 / 6 to 1 / 5 of the flow rate L2. The continuous quenching time t1 of L1 follows the following formula: t1 = 227.6×C+74.5×Si+11.5×(1.2×Cr+1.8×Mo+Ni)+54.6×V-82.3. The technical solution of the present invention can reduce the hardness of the near-surface layer of the wheel tread, and basically does not reduce the internal hardness of the sub-surface layer of the tread and the rim; the cross-sectional hardness range of the wheel of the present invention is less than 20HB, which meets the requirements of a narrow hardness range, and can meet the requirements of urban rail vehicles for wheel performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of railway wheel preparation, and in particular relates to a wheel with reduced hardness of a tread near the surface layer and a production method thereof. Background Art

[0002] Wheels are called the "shoes" of rail transit and are key running components of rail vehicles. Their performance directly affects the service performance of wheels. With the improvement of rail transit, the market competition for rail transit wheels is becoming increasingly fierce, and the requirements for wheel performance are getting higher and higher. Simply improving hardness and wear resistance cannot meet the needs of wheel operation.

[0003] During the service life of the wheels, the repeated effects of wheel-rail contact stress and vibration impact may cause surface damage such as non-roundness, which will directly affect the smoothness of vehicle operation, reduce riding comfort, and in severe cases lead to operational safety problems.

[0004] Studies have shown that the surface damage of wheel treads is closely related to wheel steel material factors such as the hardness level, hardening rate and depth of the hardened layer in the wheel-rail contact area. However, this correlation is not a simple increasing or decreasing relationship. Through user-side practice big data feedback, on certain subway lines in some cities in China, the lower hardness of the wheel tread near the surface may help improve problems such as early wheel non-roundness. Therefore, a well-known domestic rail vehicle company recently proposed special supply requirements for wheels with a narrow hardness range and low tread near the surface hardness.

[0005] The general heat treatment of railway wheels adopts overall heating + continuous water spraying on the tread surface for strong cooling (spray quenching) + overall tempering. In the spray quenching stage, due to the large cross-section of the rim, the cooling rate changes sharply in the radial direction, which will inevitably lead to a gradient change in the spacing of pearlite sheets in the radial direction, resulting in a significant radial hardness gradient, and the hardness shows a monotonically decreasing trend from the surface to the inside. Under the existing technology, the hardness difference range between the near-surface layer (i.e. within 10mm from the tread) and the wear limit (i.e. 35mm from the finished tread) of the commonly used existing brands of urban rail vehicle wheels is likely to exceed 30HB. From the tread inward, the hardness shows a monotonically decreasing trend, which cannot meet the special supply requirements of wheels with a narrow hardness range. Summary of the invention

[0006] The object of the present invention is to provide a wheel with reduced hardness of the near-surface layer of the tread and a production method thereof, which can reduce the hardness of the near-surface layer of the wheel tread and basically do not reduce the internal hardness of the sub-surface layer of the tread and the rim; meet the requirements of a narrow hardness range, and the produced wheels can meet the requirements of urban rail vehicles for wheel performance.

[0007] The specific technical solutions of the present invention are as follows:

[0008] A method for producing a wheel with reduced hardness of the tread surface near the surface, using intermittent spray quenching of the tread surface;

[0009] Preferably, the intermittent quenching method for the tread is: adopting "weak-stop-strong" intermittent quenching cooling, specifically: first use flow rate L1 to spray quench the wheel tread, after the flow rate L1 spray quenching is completed, the wheel is left to stand at natural ambient temperature for 5 to 15 seconds, and then switched to flow rate L2 to spray quench the wheel tread; flow rate L1 is 1 / 6 to 1 / 5 of flow rate L2.

[0010] Preferably, the method for producing a wheel with reduced hardness of the tread near the surface layer comprises the following steps:

[0011] S1: putting the rolled blank wheel into the furnace for heating and heat preservation;

[0012] S2: The wheel is quenched by intermittent tread spray quenching, and the wheel rotates during the spray quenching process;

[0013] S3: The wheel is transferred to a tempering furnace for tempering treatment.

[0014] Step S1 is specifically as follows: heating the wheel to Ac3+(60-90)°C and keeping the temperature for 1-1.5h; ensuring that the entire wheel is evenly heated and fully austenitized.

[0015] The intermittent quenching method of the tread in step S2 is to adopt "weak-stop-strong" intermittent heat treatment cooling: first, the wheel tread is quenched with flow rate L1. After the quenching with flow rate L1 is completed, the wheel is left to stand at natural ambient temperature for 5 to 15 seconds, and then the flow rate is increased and quenched with flow rate L2. The continuous quenching time t2 is 210 to 270 seconds.

[0016] Preferably, for a wheel with a rim thickness B≤75 mm of a blank wheel, the flow rate L2 is controlled to have a quenching time t2 of: 210 s≤t2≤240 s;

[0017] For wheels with a rim thickness of B>75mm, control the flow rate L2 and the quenching time t2: 240s<t2≤270s.

[0018] The flow rate of the flow rate L1 is 1 / 6 to 1 / 5 of the flow rate L2, that is, the smaller flow rate L1 is controlled as follows: the water flow rate of each spray gun is 3 to 4 m 3 / h, the flow rate L1 continuous quenching time t1 is 60 to 110s, and the specific flow rate L1 continuous quenching time t1 follows the following formula:

[0019] t1=227.6×C+74.5×Si+11.5×(1.2×Cr+1.8×Mo+Ni)+54.6×V-82.3;

[0020] In the formula, the index value of each element = the content of the element in the steel × 100; the unit of t1 is s.

[0021] The wheel structure must be ferrite + pearlite, which is a prerequisite. If a single flow rate L2 is used for forced cooling, the actual cooling rate of the tread near the surface is extremely high, exceeding 20°C / s, and non-pearlite harmful structures will inevitably be generated and need to be removed. The elements C, Cr, Mo, and V in the wheel steel can improve the hardenability of the steel and increase the depth of non-pearlite harmful structures during quenching. Changing the traditional large-flow L2 direct injection and adopting the "weak-stop-strong" intermittent quenching method of the present invention can well avoid the formation of non-pearlite harmful structures and reduce the hardness of the tread near the surface, killing two birds with one stone. In the composition, the higher the content of elements such as C, Cr, and Mo, the deeper the harmful structure layer, and the longer t1 needs to last. The corresponding weight coefficient is also set according to the contribution of each element to the hardenability.

[0022] In step S2, the spray quenching is specifically as follows: 6 box-type combined spray guns are evenly distributed along the circumference of the wheel, each spray gun is integrated by a combination of two water outlet branches with flow rates L1 and L2, each branch pipe is independently controlled to discharge water, and the water outlet flow rate of each spray gun is equal, that is, the flow rate L2 of each spray gun is 18-20m 3 / h, water outlet speed 6~8m / s;

[0023] In step S2, the wheel rotates during the quenching process, and the wheel rotation angular velocity is 55-65° / s.

[0024] In step S2, the water discharge direction of the spray gun is along the rotation direction of the wheel, and the water column and the tread tangent form an angle of 30 to 35 degrees.

[0025] In step S2, ensure that the transition area between the rim and the spoke is dark, and complete the cooling structure transformation inside the rim. The rolled steel integral wheel requires the rim to have good hardness and wear resistance, while the spoke is required to have high plasticity and toughness, so the structure control at the transition between the two is also very important. In other words, this position should be used as an important reference when preparing the wheel by heat treatment to ensure that the entire rim effective area (i.e. within the wear limit) has completed the structure transformation.

[0026] After quenching, the surface temperature of the wheel tread is lower than 100℃, ensuring that the entire rim area is worn to the limited area and the pearlite structure transformation is completed.

[0027] like Figure 2As shown, after the overall austenitization of the wheel is uniformly heated, the wheel tread is first spray-quenched with a relatively small flow rate for a certain period of time; compared with the traditional large-flow forced spray-quenching, the tread near the surface undergoes a coarser pearlite + ferrite transformation due to the reduction in cooling rate; then the spray-quenching is stopped, and the tread is left to stand for a short time at the natural ambient temperature, so that the temperature of the boundary between the tread near the surface and the inner part of the rim rises slightly; then it is switched to large-flow forced cooling, so that the metal inside the rim that has not been transformed will then complete the pearlite + ferrite transformation. The present invention adopts a "weak-stop-strong" intermittent tread cooling method to achieve the effect of "reverse gradient cooling", optimize the cross-sectional hardness distribution of the wheel rim, and solve the problem of a large hardness gradient caused by the "large cooling gradient" of traditional tread spray-quenching.

[0028] Step S3 is: transporting the wheel obtained in step S2 to a tempering furnace for tempering treatment; the cooling bed transfer time is 5 to 8 minutes;

[0029] In step S3, the tempering temperature is controlled to be lower than 500° C. and kept warm for 2.5 to 3 hours.

[0030] After tempering, the wheel is taken out and air-cooled, and the finished wheel is obtained through subsequent machining and other processes. Specifically, the rim surface is cut and machined using a circular blade with a diameter of φ20 to φ25 mm. The total radial machining volume of the single-sided tread is 6 to 9 mm, the machining line speed is 170±20 m / min, the cutting depth is 0.4 to 0.6 mm per cut, the feed rate is 0.8 to 1.0 mm per revolution, and the roughness Ra of the finished tread is 3.2 to Ra 6.3.

[0031] The present invention provides a wheel with reduced hardness of a tread near the surface, comprising a wheel having the following components by mass percentage:

[0032] C 0.54~0.63%, Cr 0.12~0.30%, Mo 0.04~0.10%, Ni 0.05~0.10%, V 0.02~0.06%.

[0033] Preferably, the wheel with reduced hardness of the tread near the surface layer comprises a wheel having the following mass percentage components:

[0034] C 0.54~0.63%, Si 0.20~0.40%, Mn 0.70~0.80%, Cr 0.12~0.30%, Mo0.04~0.10%, Ni 0.05~0.10%, V 0.02~0.06%, P≤0.020%, S≤0.015%, and the rest are Fe and unavoidable impurities.

[0035] The microstructure of the wheel produced by the present invention at room temperature is pearlite + a small amount of ferrite. When the wheel is worn to the limit, that is, the average ferrite volume fraction at 35mm away from the finished tread is 3% to 6%, the average pearlite sheet spacing is 140 to 180nm, and the grain size is ≥7.5. Compared with the wheel obtained by the traditional process, the pearlite structure near the surface of the wheel tread obtained by the scheme of the present invention is coarser, the ferrite volume fraction is higher, the average ferrite volume fraction is 4% to 6%, the average pearlite sheet spacing is 140 to 185nm, the grain size is ≥7.5, and the microstructure characteristics are equivalent to the average sheet spacing and ferrite volume fraction of the pearlite structure at the wear limit. The hardness obtained by the present invention is lower. Compared with the traditional process, the hardness of the wheel tread near the surface is reduced by 7% to 10%, while the pearlite structure morphology and hardness of the sub-surface of the tread and the inside of the rim are almost unchanged, the cross-sectional hardness range is reduced by 30% to 50%, and the cross-sectional hardness range is less than 20HB, reaching the design expectation of a narrow hardness range.

[0036] Some descriptions are explained in the present invention:

[0037] 1) The wheel tread near surface layer mentioned in the present invention refers to the area within 10 mm from the tread, the wheel tread sub-surface layer refers to the area 10-15 mm from the tread, and the inside of the rim refers to the area near the wear limit, i.e., 35 mm from the tread.

[0038] 2) The cross-sectional hardness range described in the present invention refers to the absolute difference between the maximum hardness and the minimum hardness on the cross-sectional surface of the wheel rim. For the convenience of calculation, the hardness difference between 5mm from the finished tread and 35mm from the tread is generally taken. The hardness of the near-surface layer is reduced by 7% to 10% by the present invention. The maximum hardness may appear in the near-surface layer or in the sub-surface layer, but the position where the minimum hardness appears remains unchanged, which is still inside the rim. The calculation method of the cross-sectional hardness range is still the maximum hardness minus the minimum hardness. If the maximum hardness appears in the sub-surface layer, the hardness difference between the sub-surface layer (15mm from the finished tread) and the hardness at 35mm from the tread is taken.

[0039] 3) The narrow hardness range refers to the cross-sectional hardness range of the wheel rim. The cross-sectional hardness range of the present invention is less than 20HB, meeting the narrow hardness range requirement.

[0040] If the quenching stage of the present invention adopts the method of first weak and then strong, the weak cooling in the first stage takes away part of the heat, reducing the overall heat storage, thus generating a "pre-cooling effect" during the weak-strong alternation, and then coupled with the strong cooling in the second stage, so that cooling concentration is formed in a smaller range of the tread sub-surface layer, increasing the effective cooling rate in the area, causing local structural performance non-uniformity. The present invention briefly stops during the weak-strong alternation, and the short-term temperature recovery makes the temperature distribution in the second stage more uniform, which can reduce or eliminate the problem of local cooling non-uniformity caused by "temperature drop inertia". By adopting the technical solution of the present invention, the hardness of the tread near the surface layer is reduced without changing the hardness of other parts of the rim, thereby narrowing the radial hardness range of the wheel rim; by reducing the hardness of the near-surface layer, the present invention is conducive to improving the early service performance of newly installed wheels, quickly obtaining a relatively optimal wheel-rail profile geometric dimension match during the running-in stage, and reducing the probability of non-circularity; at the same time, the narrow rim hardness range achieved by the present invention is conducive to improving the wear stability and uniformity of the wheel throughout its life cycle, reducing the frequency of unplanned turning and repair, extending the service life of the wheel, and reducing the line operation and maintenance costs; and the process flow of the present invention is simple and easy, and can be implemented without the need for production line equipment modification, thereby facilitating industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Schematic diagram of the microstructure distribution at different depths of the wheel rim obtained by the traditional high-flow spray quenching process;

[0042] Figure 2 A schematic diagram of the microstructure distribution at different depths of the wheel rim obtained by the "weak-stop-strong" intermittent tread cooling process of the present invention;

[0043] Figure 3 The radial hardness distribution at the nominal rolling circle of the wheels of Example 1 and Comparative Example 1;

[0044] Figure 4 The radial hardness distribution at the nominal rolling circle of the wheels of Example 2 and Comparative Example 2;

[0045] Figure 5 This is the metallographic structure of the wheel tread near the surface (3 to 7 mm from the tread) of Example 2, in which the volume fraction of ferrite is relatively high, which is 4.8±0.2%;

[0046] Figure 6 This is the scanning electron microscope structure of the wheel tread near the surface (3 to 7 mm from the tread) of Example 2. The pearlite structure is coarse and the interlamellar spacing is 164±3 nm.

[0047] Figure 7 This is the metallographic structure of the wheel in Example 2 that has been worn to the limit (30-40 mm from the tread), and the ferrite volume fraction is relatively high, which is 4.6±0.2%;

[0048] Figure 8 This is the scanning electron microscope structure of the wheel in Example 2 that was worn to the limit (30-40 mm from the tread), the pearlite structure is coarse, and the interlamellar spacing is 160±3 nm;

[0049] Fig. 9 This is the metallographic structure of the wheel tread near the surface (3 to 7 mm from the tread) of Comparative Example 2, in which the ferrite content is relatively low, less than 3%, and the spacing between pearlite sheets is relatively fine;

[0050] Fig.10 This is the metallographic structure of the wheel in comparative example 2 that was worn to the limit (30-40 mm from the tread), with a relatively high ferrite content of 4.7±0.3%, and a relatively coarse spacing between pearlite sheets;

[0051] Fig.11 The radial hardness distribution at the nominal rolling circle of the wheels of Example 3 and Comparative Example 3;

[0052] Fig.12 The Vickers hardness distribution of the wheel tread in the middle of the wheel tread in the radial direction under a small load in Comparative Example 4, Example 2 and Comparative Example 2 shows that the solution of the present invention can reduce or eliminate the problem of uneven local cooling caused by the "pre-cooling effect";

[0053] Fig.13 The microstructure of the wheel of comparative example 5, the shaded part in the figure is a schematic diagram of harmful non-pearlite structures. When the intermittent tread cooling of "weak-stop-strong" is adopted, due to insufficient weak cooling time, a mixed structure interlayer of "ferrite + pearlite and upper bainite" appears on the sub-surface of the tread;

[0054] Fig.14 The radial hardness distribution at the nominal rolling circle of the wheel of Example 6, Example 3 and Comparative Example 3 shows that when the "weak-stop-strong" intermittent tread cooling is adopted, the hardness of the tread subsurface and the inside of the rim decreases due to the excessive weak cooling time. DETAILED DESCRIPTION

[0055] The scheme of the present invention is described in detail with reference to the accompanying drawings and embodiments.

[0056] Example 1

[0057] A wheel with reduced hardness of the tread near the surface comprises the following components in mass percentage: as shown in Table 1, P 0.011% in the steel component; S 0.011%; the raw materials not shown in Table 1 are Fe and unavoidable impurities.

[0058] The production method of a wheel with reduced hardness of the tread near the surface layer of Example 1 comprises the following specific steps:

[0059] S1. Put the rolled blank wheel into the furnace and heat it to 845±10℃, and keep it evenly heated for 1h to ensure that the whole wheel is evenly heated and fully austenitized.

[0060] S2. Take out the fully austenitized wheel and transfer it to the horizontal quenching table. Use the intermittent heat treatment cooling of "weak-stop-strong". 6 box-type combination (including large and small flow control) spray guns are evenly distributed along the circumference of the wheel. The water flow rate of each spray gun is equal. The rim thickness B is 85mm. First, use the smaller flow rate L1 to spray quench the wheel tread. The flow rate of each spray gun is 4m 3 / h, and the continuous quenching time t1 is 63s. During the quenching process, the wheel rotates at an angular velocity of 65° / s, the water outlet direction is along the direction of wheel rotation, and the water column and the tread tangent are at an angle of 35°. After the small flow quenching is completed, the wheel is left at natural ambient temperature for 15s, and then the flow rate is switched to a large flow rate L2 of 20m 3 / h, strong quenching with a water outlet speed of 8m / s, and continuous quenching time t2 of 270s, ensure that the transition area between the rim and the spoke plate is darkened and the cooling structure transformation inside the rim is completed.

[0061] S3, after the quenching, the wheel is transferred to the tempering furnace through the cooling bed for 7 minutes, and then the wheel is loaded into the tempering furnace and the uniform temperature T is adopted. 回 After tempering at 490℃, the wheel was taken out and air-cooled, and the wheel rim surface was machined with a circular blade of φ20mm in diameter. The total machining amount of the single-side tread was 6.5mm, the machining line speed was 150m / min, the cutting depth was 0.4mm per cut, the feed rate was 0.9mm per revolution, and the finished tread roughness was Ra 6.2.

[0062] Table 1 Main chemical components and technical parameters of wheels of the embodiment and comparative example (wt%)

[0063]

[0064]

[0065] Comparative Example 1

[0066] A wheel comprises the following components in mass percentage: as shown in Table 1, in the steel composition, P 0.012%; S 0.011%; the raw materials not shown in Table 1 are Fe and unavoidable impurities.

[0067] The preparation steps and relevant technical parameters of the wheel are the same as those of Example 1, but different from Example 1 is that the continuous L2 used in step S2 quenching in Comparative Example 1 is 20m 3 / h large flow rate spray quenching, duration 320s.

[0068] The radial hardness distribution of the nominal rolling circle of the wheels of Example 1 and Comparative Example 1 is as follows Figure 3As shown. The radial hardness gradient of the wheel of comparative example 1 is obvious, and the hardness difference between the tread surface and the inside of the rim is 26HB, while the hardness of the tread surface of the wheel of embodiment 1 is significantly reduced, and the gradient is not obvious. The hardness difference between the tread surface and the inside of the rim is only 18HB, and the hardness of the tread sub-surface and the inside of the rim is equivalent to that of the wheel of comparative example 1, achieving the design expectation. The microstructure of the wheel of embodiment 1 at room temperature is pearlite + a small amount of ferrite. The ferrite content at the wear limit (i.e. 35mm away from the finished tread) is 5.7±0.2%, the pearlite interlamellar spacing is 174±3nm, and the grain size is 8.5.

[0069] The tensile mechanical properties and Charpy impact energy of the wheel rim of Example 1 and Comparative Example 1 are shown in Table 2. It can be seen that the adoption of the scheme of the present invention has little effect on the conventional mechanical properties of the key parts of the wheel rim, and can ensure the service safety of the wheel.

[0070] Table 2 Main mechanical properties of the wheel rim of the embodiment and the comparative example

[0071]

[0072]

[0073] Example 2

[0074] A wheel with reduced hardness of the tread near the surface comprises the following components in mass percentage: as shown in Table 1, P 0.009% and S 0.010% in the steel component; the raw materials not shown in Table 1 are Fe and unavoidable impurities.

[0075] The production method of a wheel with reduced hardness of the tread near the surface layer of Example 2 comprises the following specific steps:

[0076] S1. Put the rolled blank wheel into the furnace and heat it to 850±10℃, and keep it evenly heated for 1h25min to ensure that the whole wheel is evenly heated and fully austenitized.

[0077] S2. Take out the fully austenitized wheels and transfer them to the horizontal quenching table. Use the intermittent heat treatment cooling of "weak-stop-strong". Six box-type combination (including large and small flow control) spray guns are evenly distributed along the circumference of the wheel. The water flow rate of each spray gun is equal. The rim thickness B is 75mm. First, use a smaller flow rate to spray quench the wheel tread. The flow rate size L1 of each spray gun is 3.5m 3 / h, and the continuous quenching time t1 is 81s. During the quenching process, the wheel rotates at an angular velocity of 60° / s, the water outlet direction is along the direction of wheel rotation, and the water column and the tread tangent are at an angle of 35°. After the small flow quenching is completed, the wheel is left at natural ambient temperature for 10s, and then switched to a flow rate L2 of 19m 3 / h, strong quenching with a water outlet speed of 7m / s, and continuous quenching time t2 of 240s, ensure that the transition area between the rim and the spoke plate is darkened and the cooling structure transformation inside the rim is completed.

[0078] S3. After the quenching, the wheel is transferred to the tempering furnace through the cooling bed for 8 minutes. Then, the wheel is loaded into the tempering furnace and tempered at an average temperature of 480℃ and kept warm for 2h40min. After the tempering, the wheel is taken out and air-cooled. The rim surface is machined with a circular blade of φ25mm in diameter. The total machining amount of the single-side tread is 8.5mm in radial direction, the machining line speed is 165m / min, the cutting depth is 0.5mm per cut, the feed rate is 0.85mm per revolution, and the finished tread roughness is Ra 6.1.

[0079] Comparative Example 2

[0080] A wheel comprises the following components in mass percentage: as shown in Table 1, P 0.010% and S 0.010% in the steel component; the raw materials not shown in Table 1 are Fe and unavoidable impurities.

[0081] The preparation steps and relevant technical parameters of the wheel are the same as those of Example 2, but different from Example 2 is that the continuous L2 used in step S2 quenching in Comparative Example 2 is 19m 3 / h large flow rate spray quenching, duration 270s.

[0082] The radial hardness distribution of the nominal rolling circle of the wheels of Example 2 and Comparative Example 2 is as follows: Figure 4 As shown. The radial hardness gradient of the wheel in comparative example 2 is obvious, and the hardness difference between the tread surface and the inside of the rim is 28HB. The hardness of the tread surface of the wheel in embodiment 2 is significantly reduced, and the gradient is not obvious. The hardness difference between the tread surface and the inside of the rim is only 19HB, and the hardness of the tread sub-surface and the inside of the rim is equivalent to that of the wheel in comparative example 2, achieving the design expectation. Take the finished wheel obtained in embodiment 2, take one sample each at a radial distance of 3 to 7 mm and 30 to 40 mm from the tread for microstructure analysis, and the results are as follows Figure 5-Figure 8 As shown. The microstructure of the wheel tread near the surface (3-7mm from the tread) of Example 2 at room temperature is pearlite + a small amount of ferrite, and the microstructure of the tread near the surface is coarse, with a ferrite content of 4.8±0.2%, a pearlite platelet spacing of 164±3nm, and a grain size of 8.0. The ferrite content of the wheel in Example 2 worn to the limit (i.e., 35mm from the finished tread) is 4.6±0.2%, the pearlite platelet spacing is 160±3nm, and the grain size is 8.0. It can be seen that the microstructural characteristics of the tread near the surface of the wheel in Example 2 are roughly equivalent to those of the inside of the rim matrix. Take the finished wheel obtained in Comparative Example 2, take one sample each at a radial distance of 3-7mm and 30-40mm from the tread for microstructural analysis, and the results are as shown Figure 9-10As shown. The ferrite content near the surface of the wheel tread of Comparative Example 2 is less than 3%, and the pearlite interlamellar spacing is 116±2nm, which is relatively fine; while the ferrite content at the wear limit is higher, 4.7±0.3%, and the pearlite interlamellar spacing is 158±3nm, which is relatively coarse. By comparison, it can be seen that the microstructures of the wheel tread near the surface of Comparative Example 2 and the inner part of the rim matrix are quite different, showing a gradient distribution law of "fine on the surface and coarse on the inside".

[0083] The tensile mechanical properties and Charpy impact energy of the wheel rim of Example 2 and Comparative Example 2 are shown in Table 2. It can be seen that the adoption of the scheme of the present invention has little effect on the conventional mechanical properties of the key parts of the wheel rim, and can ensure the service safety of the wheel.

[0084] Example 3

[0085] A wheel with reduced hardness of the tread near the surface comprises the following components in mass percentage: as shown in Table 1, P 0.011% in the steel component; S 0.009%; the raw materials not shown in Table 1 are Fe and unavoidable impurities.

[0086] The production method of a wheel with reduced hardness of the tread near the surface layer of Example 3 comprises the following specific steps:

[0087] S1. Put the rolled blank wheel into the furnace and heat it to 855±10℃, and keep it evenly heated for 1.5h to ensure that the whole wheel is evenly heated and fully austenitized.

[0088] S2. Take out the fully austenitized wheels and transfer them to the horizontal quenching table. Use the intermittent heat treatment cooling of "weak-stop-strong". 6 box-type combination (including large and small flow control) spray guns are evenly distributed along the circumference of the wheel. The water flow rate of each spray gun is equal. The rim thickness B is 70mm. First, use a smaller flow rate to spray quench the wheel tread. The flow rate size L1 of each spray gun is 3m 3 / h, and the continuous quenching time t1 is 95s. During the quenching process, the wheel rotates at an angular velocity of 55° / s, the water outlet direction is along the direction of wheel rotation, and the water column and the tread tangent are at an angle of 30°. After the small flow quenching is completed, the wheel is left at natural ambient temperature for 5s, and then switched to a flow rate L2 of 18m 3 / h, strong quenching with a water outlet speed of 6m / s, and continuous quenching time t2 of 210s, ensure that the transition area between the rim and the spoke plate is darkened and the cooling structure transformation inside the rim is completed.

[0089] S3. After the quenching, the wheel is transferred to the tempering furnace through the cooling bed for 5 minutes. Then, the wheel is loaded into the tempering furnace and tempered at an average temperature of 470℃ and kept warm for 3 hours. After the tempering, the wheel is taken out and air-cooled. The rim surface is machined with a circular blade of φ20mm in diameter. The total machining amount of the single-side tread is 8.7mm, the machining line speed is 180m / min, the cutting depth is 0.45mm per cut, the feed rate is 0.9mm per revolution, and the finished tread roughness is Ra 3.3.

[0090] Comparative Example 3

[0091] A wheel comprises the following components in mass percentage: as shown in Table 1, P 0.009% and S 0.008% in the steel component; the raw materials not shown in Table 1 are Fe and unavoidable impurities.

[0092] The preparation steps and relevant technical parameters of the wheel are the same as those of Example 3, but different from Example 3, the continuous L2 used in step S2 quenching in Comparative Example 3 is 18m 3 / h large flow rate spray quenching, duration 240s.

[0093] The radial hardness distribution of the nominal rolling circle of the wheels of Example 3 and Comparative Example 3 is as follows: Fig.11 As shown. The radial hardness gradient of the wheel of comparative example 3 is obvious, and the hardness difference between the tread surface and the inside of the rim is 36HB, while the hardness of the tread surface of the wheel of embodiment 3 is significantly reduced, and the gradient is not obvious. The hardness difference between the tread surface and the inside of the rim is only 18HB, and the hardness of the tread sub-surface and the inside of the rim is equivalent to that of the wheel of comparative example 3, achieving the design expectation. The microstructure of the wheel of embodiment 3 at room temperature is pearlite + a small amount of ferrite. The ferrite content at the wear limit (i.e. 35mm away from the finished tread) is 3.4±0.2%, the pearlite plate spacing is 145±3nm, and the grain size is 7.5.

[0094] The tensile mechanical properties and Charpy impact energy of the wheel rim of Example 3 and Comparative Example 3 are shown in Table 2. It can be seen that the adoption of the scheme of the present invention has little effect on the conventional mechanical properties of the key parts of the wheel rim, and can ensure the service safety of the wheel.

[0095] Comparative Example 4

[0096] The chemical composition of the wheel of Comparative Example 4 is the same as that of Example 2. The preparation steps and relevant technical parameters of the wheel are the same as those of Example 2, but the difference from Example 2 is that Comparative Example 4 omits the step of "standing the wheel at natural ambient temperature for 10 seconds" in Example 2, that is, only a "weak-strong" cooling treatment is performed without a short intermediate air cooling.

[0097] High-throughput small-load Vickers hardness distribution can intuitively reflect the local microstructure and performance differences. Fig.12 The wheels of Comparative Example 4, Example 2 and Comparative Example 2 were subjected to a small load Vickers hardness test along the radial direction in the middle of the tread, with a pressing load of 9.8N and a test point spacing of 2mm. Fig.12 It can be seen that compared with Comparative Example 2, Comparative Example 4 is the same as Example 2, and can reduce the hardness of the near-surface layer of the tread to a certain extent. The layer within 10 mm is a weak cooling influence layer, and about 10 to 15 mm is a transition zone between weak and strong cooling. In the sub-surface layer and the interior 15 to 30 mm away from the tread, it can be seen that there is a large difference in hardness between Comparative Example 4 and Comparative Example 2. This is because strong cooling is immediately carried out after weak cooling, and a "pre-cooling effect" is generated during the weak-strong alternation, which is then coupled and superimposed with strong cooling, resulting in cooling concentration within this range, and the effective cooling rate is increased, resulting in local structural performance unevenness. By performing a short period of air cooling in the middle, the temperature distribution in the strong cooling stage can be made more uniform by returning to temperature, thereby reducing or eliminating the problem of local cooling unevenness caused by "temperature drop inertia". Fig.12 As shown, in the sub-surface layer and the interior layer 15 to 30 mm away from the tread, the hardness difference at the same depth between the wheels of Example 2 and Comparative Example 2 is very small, and the hardness decreases gently with the depth of the tread. The local high hardness area caused by the "pre-cooling effect" is basically eliminated. In other words, the use of the scheme of the present invention can well ensure the cooling uniformity of the sub-surface layer of the tread and the interior of the rim.

[0098] Comparative Example 5

[0099] The chemical composition of the wheel of comparative example 5 is the same as that of example 3. The preparation steps and relevant technical parameters of the wheel are the same as those of example 3, but the difference from example 3 is that the weak cooling time of comparative example 5 is shorter, set to 80s, which does not meet the limiting formula of the weak cooling time t1 of the wheel with a given chemical composition of the present invention. After dissection and detection, it was found that a certain amount of upper bainite harmful tissue residue existed near the surface of the wheel tread, which was a mixed tissue of "ferrite + pearlite and upper bainite", as shown in FIG. Fig.13 .

[0100] Comparative Example 6

[0101] The chemical composition of the wheel of comparative example 6 is the same as that of example 3. The preparation steps and relevant technical parameters of the wheel are the same as those of example 3, but the difference from example 3 is that the weak cooling time of comparative example 6 is excessive and is set to 115s, which does not meet the limiting formula of the weak cooling time t1 of the wheel with a given chemical composition of the present invention. The hardness of the subsurface layer of the wheel tread and the inside of the rim has decreased after dissection and inspection. Fig.14 This is because the excessively long weak cooling treatment increases the weak cooling affected layer, causing a significant drop in temperature of the tread subsurface and the inside of the rim, entering the two-phase region of austenite γ and ferrite α, and excessive precipitation of ferrite, which ultimately leads to a decrease in the overall hardness level.

[0102] The above reference embodiments and drawings provide a detailed description of a wheel with reduced hardness near the tread surface and a method for producing the same. This is merely illustrative and not restrictive. Several embodiments may be listed within the limited scope. Therefore, changes and modifications that do not depart from the overall concept of the present invention should fall within the scope of protection of the present invention.

Claims

1. A method for producing a wheel with reduced hardness of the tread near the surface, characterized in that: Adopt intermittent tread quenching method: First use flow L 1. Spray quenching wheel tread, flow rate L 1 After the quenching is completed, let the wheel stand at natural ambient temperature for 5 to 15 seconds, then switch to flow L 2. Spray quenching of wheel tread; flow L 1 is flow L 1 / 6~1 / 5 of 2; flow L 1 Control: The water flow rate of each spray gun is 3~4 m 3 / h, flow rate L 1 Continuous quenching time t 1 is 60~110s; Injection time t 1 follows the formula: t 1=227.6×C+74.5×Si+11.5×(1.2×Cr+1.8×Mo+Ni)+54.6×V-82.3; In the formula, the index value of each element = the content of the element in the steel × 100; t 1 unit is s; The wheel with reduced hardness of the tread near the surface layer comprises a wheel having the following mass percentage components: C 0.54~0.63%, Cr 0.12~0.35%, Mo 0.04~0.10%, Ni 0.05~0.10%, V 0.02~0.06%.

2. The production method according to claim 1, characterized in that The method for producing a wheel with reduced hardness of the tread near the surface layer comprises the following steps: S1: putting the rolled blank wheel into the furnace for heating and heat preservation; S2: The wheel is quenched by intermittent tread spray quenching, and the wheel rotates during the spray quenching process; S3: The wheel is transferred to a tempering furnace for tempering treatment.

3. The production method according to claim 2, characterized in that: Step S1 is specifically: heating the wheel to A c3+(60~90)℃, and keep warm for 1~1.5h.

4. The production method according to claim 2, characterized in that: Spray at flow rate L2, continuous spray time t 2 is 210~270s; flow L 2 is 18~20m 3 / h, water outlet speed 6~8m / s.

5. The production method according to claim 2 or 4, characterized in that: For the rim thickness of the blank wheel B Wheels ≤75mm, flow control L 2. Quenching time t 2: 210s ≤ t 2≤240s; For the rim thickness of the blank wheel B >75mm wheels, flow control L 2. Quenching time t 2: 240s< t 2≤270s.

6. The production method according to claim 2 or 3, characterized in that: In step S2, the spray quenching is specifically as follows: the spray quenching is specifically as follows: 6 box-type combined spray guns are evenly distributed along the circumference of the wheel; and the water flow rate of each spray gun is equal.

7. The production method according to claim 2 or 3, characterized in that: In step S2, the water discharge direction of the spray gun is along the rotation direction of the wheel, and the water column forms an angle of 30-35° with the tangent line of the tread.

8. The production method according to claim 2 or 3, characterized in that: In step S2, the wheel rotates at an angular velocity of 55-65° / s.

9. A wheel with reduced hardness of the tread near the surface produced by the production method according to any one of claims 1 to 8.

10. The wheel according to claim 9, characterized in that The microstructure of the wheel at room temperature is pearlite + a small amount of ferrite, the average ferrite volume fraction 35mm away from the finished tread is 3%~6%, the average pearlite plate spacing is 140~180nm, and the grain size is ≥7.5; the average ferrite volume fraction near the surface of the wheel tread is 4%~6%, the average pearlite plate spacing is 140~185nm, and the grain size is ≥7.

5.

11. The wheel according to claim 9 or 10, characterized in that The cross-sectional hardness range of the wheel is less than 20HB.

Citation Information

Patent Citations

  • Thermal treatment method for high-carbon steel train wheel circular rim surface and heat treatment apparatus

    CN101270408A

  • Bainite steel wheel for high-tenacity rail transit and manufacture method thereof

    CN106048430A